1998
DOI: 10.1002/etc.5620170920
|View full text |Cite
|
Sign up to set email alerts
|

Profenofos toxicity to the eastern rainbow fish (Melanotaenia duboulayi)

Abstract: Abstract-The 96-h median lethal concentration for profenofos in the Australian eastern rainbow fish (Melanotaenia duboulayi) was 0.9 mg/L, corresponding with an 83% reduction in acetylcholinesterase (AChE) activity in fish head. This is an order of magnitude less sensitive than the figure reported for crucian carp (Carassius carassius). Higher lethal body burdens were found in rainbow fish exposed to high concentrations of profenofos but the inhibition of AChE activity in these fish was less than in those kill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 38 publications
0
8
0
4
Order By: Relevance
“…The inhibition of AChE has often been associated with increased swimming activity or hyperactivity. For example, Kumar and Chapman [57] found increased swimming activity in eastern rainbow fish (Melanotaenia duboulayi) exposed to the OP pesticide profenofos for 10 d. Bretaud et al [3] found similar results with goldfish (Carassius auratus) following 4h exposures to carbofuran; in fact, increased locomotor activity was detectable at an exposure concentration that was lower than the concentration inhibiting AChE activity. Work with salmon and swimming activity, however, is in contrast to the above studies.…”
Section: Relationship Between Ache Activity and Swimmingmentioning
confidence: 97%
“…The inhibition of AChE has often been associated with increased swimming activity or hyperactivity. For example, Kumar and Chapman [57] found increased swimming activity in eastern rainbow fish (Melanotaenia duboulayi) exposed to the OP pesticide profenofos for 10 d. Bretaud et al [3] found similar results with goldfish (Carassius auratus) following 4h exposures to carbofuran; in fact, increased locomotor activity was detectable at an exposure concentration that was lower than the concentration inhibiting AChE activity. Work with salmon and swimming activity, however, is in contrast to the above studies.…”
Section: Relationship Between Ache Activity and Swimmingmentioning
confidence: 97%
“…Fonofos, a phosphonodithioate insecticide also known as dyfonate, is primarily applied to control insects in a number of crops and in turfs [4,17]. Profenofos is a phosphorothiolate OP compound that has been widely used in cotton-growing areas in most countries worldwide [22]. Crotoxyphos is a phosphate used as contact and stomach poison, primarily for pests on lactating dairy and beef cattle [4].…”
Section: Enantiomer Resolutionmentioning
confidence: 99%
“…Two commonly studied biochemical biomarkers in invertebrates are cholinesterase (ChE) and glutathione-S-transferase (GST) activity. Inhibition of ChE activity has been proposed as an effective tool for monitoring the exposure of organisms to organophosphorus and carbamate pesticides [9,10], whereas induction of GST can be suggestive of exposure to organochlorine compounds [11,12]. However, recent evidence suggests that the specificity of ChE as an indicator of exposure to organophosphorus and carbamate pesticides should be questioned, because heavy metals, surfactants, and pyrethroid pesticides can inhibit ChE activity [13,14].…”
Section: Introductionmentioning
confidence: 99%